Estradiol-to-follicle ratio on human chorionic gonadotropin day is a novel predictor of gestational diabetes mellitus in women receiving fresh embryo transfer - Chen, Huijun; Liu, Yvonne; Xu, Xiangwang; Hu, Liang; Cai, Sufen; Gong, Fei; Lin, Ge; Kalk, Philipp; Krämer, Bernhard K.; Hocher, Berthold (Frontiers in Endocrinology, 2024)
Aims: To assess the predictive value of estradiol (E2) related parameters on the incidence of gestational diabetes mellitus (GDM) in women undergoing fresh embryo transfer.A Post-hoc analysis of a prospective cohort study.We identified an optimal E2/follicle (E2/F) ratio threshold of 246.03 pg/ml on the day of human chorionic gonadotropin (hCG) administration. Women with an E2/F ratio exceeding this threshold had significantly lower rates of GDM (12.75% vs. 20.41%, P < 0.001) and ovarian hyperstimulation syndrome (OHSS) (11.75% vs.15.48%, P = 0.03). Additional E2 parameters were also evaluated: baseline E2, E2 on hCG day, E2 increase, and E2 fold change. Lower GDM rates were observed in women with baseline E2 above 31.50 pg/ml (13.51% vs. 19.42%, P ＜0.01), E2 on hCG day above 3794.50 pg/ml (12.26% vs. 19.32%, P < 0.001), and E2 increase above 3771.50 pg/ml (12.24% vs. 19.28%, P < 0.001). There were no significant differences in OHSS rates for these additional E2 parameters. After adjusting for confounders, lower E2/F ratio (OR: 1.626, 95% CI: 1.229-2.150, P ＜0.01), E2 on hCG day (OR: 1.511, 95% CI: 1.133-2.016, P = 0.01), and E2 increase (OR: 1.522, 95% CI: 1.141-2.031, P ＜ 0.01) were identified as risk factors for GDM.This study demonstrates that an E2/F ratio over 246.03 pg/ml is significantly associated with a reduced risk of both GDM and OHSS in women undergoing fresh embryo transfer, highlighting the E2/F ratio as a superior predictive biomarker compared to other E2-related parameters.